TRANSFIGURED LEADERSHIP: KEPEMIMPINAN ALKITABIAH SEBAGAI FONDASI MITIGASI RISIKO DIGITAL - Wahju Astjarjo Rini; Andreas Fernando; Carolina Etnasari Anjaya (Sekolah Tinggi Teologi Arastamar Bengkulu, 2024)
In an increasingly digital era, Christian leaders face new challenges in managing digital risks. To face these challenges, Christian leadership needs to be based on the spiritual values ​​contained in the event of Christ's transfiguration. This article explores the meaning of Christ's transfiguration and its implications for contemporary Christian leadership. The concept of